2015
DOI: 10.1590/s1806-66902015000100016
|View full text |Cite
|
Sign up to set email alerts
|

Mn foliar sobre a qualidade sanitária e lignina de sementes de soja convencional e resistente ao glifosato1

Abstract: RESUMO -O Mn pode estar associado à resistência das plantas aos fungos, por meio da lignificação ou inibição direta. Objetivou-se neste trabalho avaliar a aplicação foliar de Mn sobre a incidência de fungos, teores de Mn e de lignina nas sementes de soja oriundas de cultivares convencionais e de suas derivadas transgênicas resistentes ao glifosato (RR). O ensaio foi conduzido na Universidade Federal de Lavras, em blocos casualizados, com três repetições e esquema fatorial 4 x 4 x 2, sendo quatro cultivares de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
(14 reference statements)
1
4
0
1
Order By: Relevance
“…Therefore, the results of this experiment may be due to the significant increase in the AcPAL gene in the kiwifruit stem after sulfur application, which is involved in lignin synthesis and significantly increases the cell wall strength, thus hindering the invasion of Psa and disease. This is similar to the results obtained in the previous studies related to the control of pear fruit diseases by calcium [61], the improvement of rice sheath blight resistance by silicon [62], and the significant reduction in the incidence of soybean wilt, Fusarium, and Aspergillus by manganese [63]. Moreover, another mechanism by highlighted bacteria could spread in the plants was through the reproduction and secretion of bacterial fluid in the xylem, thereby blocking the ducts of plants to cause the disease [57,64].…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the results of this experiment may be due to the significant increase in the AcPAL gene in the kiwifruit stem after sulfur application, which is involved in lignin synthesis and significantly increases the cell wall strength, thus hindering the invasion of Psa and disease. This is similar to the results obtained in the previous studies related to the control of pear fruit diseases by calcium [61], the improvement of rice sheath blight resistance by silicon [62], and the significant reduction in the incidence of soybean wilt, Fusarium, and Aspergillus by manganese [63]. Moreover, another mechanism by highlighted bacteria could spread in the plants was through the reproduction and secretion of bacterial fluid in the xylem, thereby blocking the ducts of plants to cause the disease [57,64].…”
Section: Discussionsupporting
confidence: 91%
“…According to Dantas et al (2012), there is no interference of the lignin content of the seed coat on the resistance to infection by the fungus Aspergillus flavus. Carvalho et al (2015) evaluated the effect of lignin and Mn leaf application on the incidence of fungi and found that the cultivar BRS Celeste had the lowest lignin content and was among those with the lowest incidence of Aspergillus flavus, inferring that the highest lignin content in the seed coat of soybean seeds do not result in increased resistance to infection.…”
Section: Resultsmentioning
confidence: 99%
“…No significant interaction was found between tested factors for lignin content, but soybean addition in single-row treatments (trial 1) increased such levels compared to standard corn silage (Table 3). The soybean seed coat is lignin-rich, which might have increased this polymer content in silages (CARVALHO et al, 2015), as soybean participation in ensiled mass was higher in trial 1 than was in trial 2 (Table 2).…”
Section: Resultsmentioning
confidence: 99%